Integrated Structural Health Assessment Using Piezoelectric Active Sensors - Jeannette R. Wait; Gyuhae Park; Charles R. Farrar (Shock and Vibration)
This paper illustrates an integrated approach for identifying structural damage. The method presented utilizes piezoelectric (PZT) materials to actuate/sense the dynamic response of the structures. Two damage identification techniques are integrated in this study, including impedance methods and Lamb wave propagations. The impedance method monitors the variations in structural mechanical impedance, which is coupled with the electrical impedance of the PZT patch. In Lamb wave propagations, one PZT patch acting as an actuator launches an elastic wave through the structure, and responses are measured by an array of PZT sensors. The changes in both wave attenuation and reflection are used to detect and locate the damage. Both the Lamb wave and impedance methods operate in high frequency ranges at which there are measurable changes in structural responses even for incipient damage such as small cracks, debonding, or loose connections. The combination of the local impedance method with the wave propagation based approach allows a better characterization of the system’s structural integrity. The paper concludes with experimental results to demonstrate the feasibility of this integrated active sensing technology.